Animal Genetics and Diseases: Advances in Farming and Livestock Systems - Fife, Mark S.; Hammond, John A.; Doeschl-Wilson, Andrea B. (Frontiers Media SA, 2020)
Proceedings of the new Animal Genetics and Disease Wellcome Genome Campus meeting. The new Animal Genetics and Disease 2017 conference committee organised a Research Topic for the proceedings of this inaugural conference. The meeting brought together specialists working on the interface between genomics, genetic engineering and infectious disease with the aims of improving animal and human health and welfare. This conference was funded by Advanced Courses and Scientific Conference at the Wellcome Genome Campus, Hinxton, UK. The conference highlights breakthroughs in genomic technologies that are rapidly increasing our understanding of the fundamental role that host and pathogen genetics play in infections and epidemics. This Research Topic focuses on how infections spread and how they further affect the productivity of livestock systems and food supply chains. Thanks to technological advances, we now have the tools for real-time surveillance of zoonoses affecting wildlife, farm animals and animal-to-human disease transmission.